2008
DOI: 10.1029/2007jf000795
|View full text |Cite
|
Sign up to set email alerts
|

Bedform transport rates for the lowermost Mississippi River

Abstract: [1] New methods of data collection and processing are developed to provide quantitative, reach-scale measurements of bedform transport mass within the tidally influenced Mississippi River. A multibeam swath profiler was used to collect daily bathymetry over a range of water discharges, and bed elevation changes induced by dune migration are measured. These values are coupled with bulk physical properties of the bed sediment to constrain mass flux, and annual bedform transport is estimated at 2.2 Â 10 6 metric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
183
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(191 citation statements)
references
References 42 publications
6
183
0
2
Order By: Relevance
“…We then used rating curves (Allison et al, 2017) to compute the discharge of suspended sediments corresponding to each daily water discharge. The lowest flow bin is assumed to carry mud but no sand, consistent with modern observations (Nittrouer et al, 2008). Binning the data by water discharge reduces the confounding influence of hysteresis in the sediment load.…”
Section: Input Sand Fractionmentioning
confidence: 54%
“…We then used rating curves (Allison et al, 2017) to compute the discharge of suspended sediments corresponding to each daily water discharge. The lowest flow bin is assumed to carry mud but no sand, consistent with modern observations (Nittrouer et al, 2008). Binning the data by water discharge reduces the confounding influence of hysteresis in the sediment load.…”
Section: Input Sand Fractionmentioning
confidence: 54%
“…Although habitat delineations can be done manually, robust automated procedures, like the BRESS method, offer increased speed, efficiency, more objectivity, and reproducible map products. Another possible application is to improve the understanding of seafloor stability, particularly important in the coastal environment [53]. In fact, the quality of the identification of valleys and ridges within a defined range of scales makes BRESS outputs a good candidate for use in the calculation of bedform migration rates.…”
Section: Discussionmentioning
confidence: 99%
“…In the transport of sediments of the riverbed of great canals and rivers, mainly sandy ones, like the Capibaribe river, there are some difficulties, mostly because of the dynamic conditions of the riverbed-water interface, more complicated in the estuarine regions with a strong tide influence (MILLIMAN; MEADE apud NITTROUER; ALLISON;CAMPANELLA, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Given the shortage and the importance of the studies of sand transport in th riverbeds, Nittrouer, Allison and Campanella (2008) analyzed the transport of sediments of the riverbed, associated to the migration of dunes in localized areas along a section of 15 kilometers of the Mississippi river, utilizing data from the multibeam echobathymeter and river downloads. Luo et al (2007) identified the morphological and hydrological impacts of the Perl River's delta in China, caused by the extraction of sandy sediment of the riverbed, with the intent of using it in construction.…”
Section: Introductionmentioning
confidence: 99%